Government Communication as a Device for the Nationalization of the Public: Ecuador 2010: The Speech That Converted a Police Revolt in President Assassination Attempt - Córdova Del Alcázar, Gabriela (Journal of Leadership, Accountability and Ethics, 2022)
During the decade 2007-2017, Ecuador was led by a regime that identified itself as part of 21st Century Socialism. Rafael Correa came to the Presidency with a speech that questioned the traditional party system and the promise of a new Constitution that would recognize the diversity of interests of Ecuadorian society. On September 30, 2010 (30-S), a police revolt led to the retention of President Correa for several hours and ended with an armed confrontation between the police and the military that left several victims. Among them, the reorientation of government communication that distanced itself from the initial inclusive proposal to discourse of exclusion that subordinated the public to the State. This essay proposes a communicational interpretation of this transit based on the evolution of the relationship between the government and social movements and its manifestation in the official discourse about the public.